A novel strategy to synthesize dual‐responsive polymeric nanocarriers for investigating the activity and stability of immobilized pectinase. (12th February 2019) - Lei, Lei; Liu, Jiangtao; Ma, Xiao; Yang, Hong; Lei, Zhongli
Abstract: A dual‐stimuli‐responsive support material for pectinase immobilization through ionic bonding was prepared. Specifically, polystyrene‐b‐polymethylacrylic (PS‐b‐PMAA), light‐ and pH‐sensitive polystyrene‐(5‐propargylether‐2‐nitrobenzyl bromoisobutyrate)‐b‐poly(diethylamino)ethyl methacrylate‐b‐poly(polyethylene glycol methacrylate) (PS‐ONB‐PDEAEMA‐b‐PPEGMA) were synthesized through atom transfer radical polymerization, click chemistry, and hydrolysis. The two parts could self‐assemble into the micelles in an aqueous solution. The micelles shrunk at a higher pH, and their size reduced under UV irradiation. The stimuli‐responsive properties of micelles were characterized by dynamic light scattering and transmission electron microscopy. It has been found that this support was able to adsorb 10 U/mL of immobilized pectinase (approximately 223 mg/g) at pH 5.0 and 60 °C for 60 Min. Meanwhile, the highest relative activity of immobilized pectinase was up to approximately 95% at pH 5.0 and 60 °C. The immobilized pectinase retained more than 50% of the initial activity after eight cycles. The relative activity of the pectinase immobilized on the supports without UV irradiation was approximately 3% lower than that after UV irradiation at 60 °C, indicating that tailoring of enzyme activity was achieved by changing environmental conditions. Apparently, the original enzymatic support material had a great application prospect on enzyme immobilization.